Pengaruh Pengungkapan Tanggung Jawab Sosial Perusahaan dan Profitabilitas pada Nilai Perusahaan - Rita Susanti, Gusti Ayu Made; Budiasih, I Gusti Ayu Nyoman (E-Jurnal Akuntansi; Vol 28 No 3 (2019), 2019)
The purpose of this study is to prove empirically the effect of disclosure of corporate social responsibility and profitability on the value of mining companies listed on the Indonesia Stock Exchange for the period 2015-2017. Samples were selected using purposive sampling technique to obtain a total sample of 15 companies, so the number of observations with a study period of 3 years was 45 observations. The data analysis technique used is multiple linear regression analysis. After analyzing the data, the results obtained from CSR disclosure did not affect the value of the company and found a positive relationship between profitability and firm value. Keywords : Disclosure of corporate social responsibility, profitability, the value of the company.